The spatial organization of metabolism within the plant cell. - Sweetlove, L; Fernie, A (2013)
Identifying the correct subcellular locations for all enzymes and metabolites in plant metabolic networks is a major challenge, but is critically important for the success of the new generation of large-scale metabolic models that are driving a network-level appreciation of metabolic behavior. Even though the subcellular compartmentation of many central metabolic processes is thought to be well understood, recent gene-by-gene studies have revealed several unexpected enzyme localizations. Metabolite transport between subcellular compartments is crucial because it fundamentally affects the metabolic network structure. Although new metabolite transporters are being steadily identified, modeling work suggests that we have barely scratched the surface of the catalog of intracellular metabolite transporter proteins. In addition to compartmentation among organelles, it is increasingly apparent that microcompartment formation via the interactions of enzyme groups with intracellular membranes, the cytoskeleton, or other proteins is an important regulatory mechanism. In particular, this mechanism can promote metabolite channeling within the metabolic microcompartment, which can help control reaction specificity as well as dictate flux routes through the network. This has clear relevance for both synthetic biology in general and the engineering of plant metabolic networks in particular.